On the Problem of Laws in Nature and History: A Comparison - Berry, Stephan (History and theory, 1999)
In the philosophy of science there has traditionally been a tendency to regard physics as the incarnation of science per se. Consequently, the status of other disciplines has been evaluated according to their ability to produce laws resembling those of physics. This view has yielded a considerable bias in the discussion of historical laws. Philosophers as well as historians have tended to discuss such laws mostly with reference to the situation in physics; this often led to either one of two conclusions, namely that (1) history is epistemologically completely separated from natural science because it does not have universal laws, or that (2) the ultimate goal of the study of history must be the formulation of such universal laws. I maintain that neither conclusion is necessary. To substantiate this position, I discuss several aspects of natural laws. One aspect that is often neglected is that there are many kinds of statistical laws in nature; there is no close link between laws and determinism. Moreover, natural systems exist that have a history, that is, systems that are, like human history, shaped by irreversible, singular events. One important case is biological evolution; accordingly I discuss the relation between evolutionary theory and historiography. However, since we are part of the living world, and in addition to considering the methodological similarities between the two fields, one could also ask whether the laws of evolution are of direct relevance for understanding our history. This issue of history as evolution is investigated in detail in the final section of the paper.